Perbedaan Metode Three Compartement Sink dengan Air Panas dan Larutan Klorin terhadap Angka Kuman Alat Makan di RSU Queen Latifa - Rifatun Hasanah; Setyowati Setyowati; Noor Tifauzah (JURNAL NUTRISIA, 2017)
Background:One of the efforts in preventing congenital food disease is by washing the cutlery perfectly. The cutlery used by patients with infectious diseases should be noted more, because it has a risk in disease transmission through cutlery. The process of washing the cutlery for infected patients in Queen Latifa Hospital use three compartement sink method with hot water, while the three compartement sink method with clorine solvent has never been tested. Purpose: Research was to determine the difference in the number of germs in the tool was washed using three compartement sink method with hot water and with clorine solvent. Method:Types of research is experiment with rancangan percobaan acak kelompok (RAK). The object of this research is 4 plates and 4 bowls. The number of experimental units in this research were 2 treatments x 2 cutlery x 2 checks x 2 reapetitions = 16 experimental units. The analysis used independent t-test with 95% confidence level. Result :The average number of germs in the cutlery washed using the three compartment sink method with hot water was 1 x 101 cfu / cm2, whereas with chlorine solvent is 0.2 cfu / cm2. Independent test t-test shows p = 0.049 which means the hypothesis is accepted. onclusion : There are differences in the number of germs in the washing cutlery using the three compartment sink method with hot water and with chlorine solvent. Keywords: number of germs, cutlery, three compartment sink